Successful of Asnaf Entrepreneur: The Role of Knowledge, Skills, and Ability - Efri Syamsul, Bahri; Juhary, Ali; Mohd Mizan, Mohammad Aslam (2023)
Asnaf entrepreneurs who experience success prove that Zakat contributes to poverty alleviation of Mustahiq. This study desires to test the effect of knowledge, skills, and abilities variables on the Asnaf entrepreneur's success. The research design used the mono method quantitatively. Testing of the hypothesis is done by using a structural model approach. A questionnaire collected data with clustered random sampling. Respondent is Asnaf entrepreneurs who had received zakat assistance from the National Board of Zakat (Baznas). Their businesses were still running in three provinces (West Java, DKI Jakarta, and Banten). Data has been collected from the Asnaf entrepreneur analysis using the SmartPLS application. The test results on the three dimensions of competency have a positive value. The skill and ability variables significantly affect the Asnaf entrepreneur's success. The test results show an r2 value of 0.394, which indicates that 39.4% of the Asnaf entrepreneur's success factors are influenced by the three variable. Zakat management entities can respond positively to these findings by increasing the Asnaf competency. These findings become inputs in formulating strategies to perform Mustahiq transformation through the Asnaf entrepreneurial program.